The Effect of Demographic Transition on Savings, Investment, and Capital Flows - Sidabutar, Misnilawaty (Jurnal Ilmiah Administrasi Publik, 2020)
The world population, as well as Indonesia, is aging and this demographic transition influences saving, investment, and capital flows. By looking at data from 1973 to 2017, this paper finds two things. First, the relationship between age groups and saving exhibits the inverted U-shape, but only old dependency impact negatively on investment based on 104 countries’ data. The capital flows represented by current account is deficit in the young dependency, but surplus in the old dependency. Second, demographic transition in Indonesia induced an increase in savings by a higher rate than investment and caused current account surplus in this period.